2003
DOI: 10.1086/377578
|View full text |Cite
|
Sign up to set email alerts
|

Branch, Spur, and Feather Formation in Spiral Galaxies

Abstract: We use hydrodynamic simulations to investigate the response of geometrically thin, self-gravitating, singular isothermal disks of gas to imposed rigidly rotating spiral potentials. By minimizing reflection-induced feedback from boundaries, and by restricting our attention to models where the swing parameter X $ 10, we minimize the swing amplification of global normal modes even in models where Toomre's Q g $ 1 2 in the gas disk. We perform two classes of simulations: short-term ones over a few galactic revolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 38 publications
2
72
0
1
Order By: Relevance
“…Inter-arm cloud populations have been scrutinised observationally in external galaxies (Elmegreen 1980;Aalto et al 1999;Scoville et al 2001;Shetty et al 2007;Foyle et al 2010;Hughes et al 2013;Colombo et al 2014), in the Milky Way (Roman-Duval et al 2010;Moore et al 2012;Eden et al 2013) and in numerical simulations (e.g., Kim & Ostriker 2002;Chakrabarti et al 2003;Dobbs et al 2006;Shetty & Ostriker 2006;Smith et al 2014). The history of inter-arm clouds is related to so called "spurs" or "feathers" emanating from the spiral arms, which have been credited to either the growth of gravitational or magneto-Jeans instabilities preferentially perpendicular to the arm (Balbus 1988) or alternatively, to the rotational shearing of over-densities in the spiral arm itself (Dobbs et al 2006;Shetty & Ostriker 2006).…”
Section: Gmfs: Milky Way Inter-arm Clouds or Spurs?mentioning
confidence: 99%
“…Inter-arm cloud populations have been scrutinised observationally in external galaxies (Elmegreen 1980;Aalto et al 1999;Scoville et al 2001;Shetty et al 2007;Foyle et al 2010;Hughes et al 2013;Colombo et al 2014), in the Milky Way (Roman-Duval et al 2010;Moore et al 2012;Eden et al 2013) and in numerical simulations (e.g., Kim & Ostriker 2002;Chakrabarti et al 2003;Dobbs et al 2006;Shetty & Ostriker 2006;Smith et al 2014). The history of inter-arm clouds is related to so called "spurs" or "feathers" emanating from the spiral arms, which have been credited to either the growth of gravitational or magneto-Jeans instabilities preferentially perpendicular to the arm (Balbus 1988) or alternatively, to the rotational shearing of over-densities in the spiral arm itself (Dobbs et al 2006;Shetty & Ostriker 2006).…”
Section: Gmfs: Milky Way Inter-arm Clouds or Spurs?mentioning
confidence: 99%
“…Chakrabarti et al (2003) showed the development of more varied features, including branches (bifurcations) and shorter leading and trailing features (spurs / feathers), again occurring primarily near the 4:1 resonance, with the morphology of the feature dependent primarily on the level of forcing of the spiral potential. Chakrabarti et al (2003) suppose that flocculence in spiral galaxies could be due largely to such resonant features, an idea recently followed up by Lee & Shu (2012), where they investigate the possibility that higher order resonances lead to the formation of multiple spurs along the arms. There is a notable difference between the work of Lee & Shu (2012), and GMC formation by gravitational instabilities in the gas or cloud-cloud collisions (which are subsequently sheared into spurs).…”
Section: Dobbs and Babamentioning
confidence: 99%
“…Numerical simulation studies suggested several mechanisms to explain the origin of spurs. First, self-gravity was proposed as a mechanism to form spurs by Chakrabarti et al (2003). Later, Kelvin-Helmholtz instability was introduced to explain wiggle structures in the arms seen in the simulations by Wada & Koda (2004).…”
Section: Massive Cluster Formation In Spursmentioning
confidence: 99%